Type and Abundance of Phytoplankton in the PT Perkebunan Nusantara V Sei Pagar Reservoir, Perhentian Raja District, Kampar Regency, Riau Province - Yuli Suciati; Tengku Dahril; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract Phytoplankton is a primary producer organism in aquatic ecosystem and it supplies oxygen to the waters through photosynthesis process. A research aim to determine types and abundance of phytoplankton in the PTPN V Sei Pagar Reservoir has been carried out on July-August 2019. Sampling taken at three stations, namely station 1 (inlet area), station 2 (central area) and station 3 (outlet area), once/week. The water quality parameters measured were temperature, transparency, depth, pH, DO, free CO2, nitrate (NO3-) and phosphate (PO43-). Result shown there were 48 species phytoplankton that consist of 10 classes, namely Chlorophyceae (14 species), Cyanophyceae (3 species), Euglenophyceae (6 spesoies), Zygnematophyceae (5 species), Trebouxiophyceae (3 species), Dynophyceae (1 species), Cryptophyceae (1 species), Crysophyceae (1 species), Xantophyceae (1 species) and Bacillariophyceae (13 species). The abundance of phytoplankton in PTPN V Sei Pagar Reservoir ranges from 6,660-33,264 cells/L. The water quality parameters were as follows: transparency 47-54 cm, temperatures 27-29 0C, pH 6, DO 4.77-6.92 mg/L, free CO2 6.65-13.98 mg/L, phosphate 0.018-0.038 mg/L, nitrate 0.905-1.23 mg/L. Based on phytoplankton abundance, PTPN V Sei Pagar Reservoir can be categorized as oligotrophic-mesotrophic.